Whole-transcriptome sequencing reveals a vernalization-related ceRNA regulatory network in chinese cabbage (Brassica campestris L. ssp. pekinensis) - Fengyan Shi (BMC, 2021)
Abstract Background The transition from vegetative growth to reproductive growth involves various pathways. Vernalization is a crucial process for floral organ formation and regulation of flowering time that is widely utilized in plant breeding. In this study, we aimed to identify the global landscape of mRNAs, microRNAs (miRNAs), long non-coding RNAs (lncRNAs), and circular RNAs (circRNAs) related to vernalization in Chinese cabbage. These data were then used to construct a competitive endogenous RNA (ceRNA) network that provides valuable information to better understand the vernalization response. Results In this study, seeds sampled from the Chinese cabbage doubled haploid (DH) line ‘FT’ with or without vernalization treatment were used for whole-transcriptome sequencing. A total of 2702 differentially expressed (DE) mRNAs, 151 DE lncRNAs, 16 DE circRNAs, and 233 DE miRNAs were identified in the vernalization-treated seeds. Various transcription factors, such as WRKY, MYB, NAC, bHLH, MADS-box, zinc finger protein CONSTANS-like gene, and B3 domain protein, and regulatory proteins that play important roles in the vernalization pathway were identified. Additionally, we constructed a vernalization-related ceRNA–miRNA–target gene network and obtained 199 pairs of ceRNA relationships, including 108 DEmiRNA‒DEmRNA, 67 DEmiRNA‒DElncRNA, and 12 DEmiRNA‒DEcircRNA interactions, in Chinese cabbage. Furthermore, several important vernalization-related genes and their interacting lncRNAs, circRNAs, and miRNAs, which are involved in the regulation of flowering time, floral organ formation, bolting, and flowering, were identified. Conclusions Our results reveal the potential mRNA and non-coding RNAs involved in vernalization, providing a foundation for further studies on the molecular mechanisms underlying vernalization in Chinese cabbage.